Od konwencjonalizmu do normatywizmu. Kilka uwag o ewolucji poglądów teoretycznoliterackich - Drong, Leszek (Er(r)go. Teoria - Literatura - Kultura, 2006)
Leszek Drong From Conventionalism to Normativism: A Few Remarks on the Evolution of Stanley Fish's Critical Position. The essay argues for an evolutionary development of Stanley Fish's views on interpretation depsite what may seem like a surprising volte-face which many critics date back to his Professional Correctness published in 1995. Fish's early constructionism is gradually moderated in his writings by the introduction of the category of interpretive communities; his insistence on the rhetorical underpinning of all our verbal activity acquires a new dimension once we realise that the rhetoricity of public discourse is curbed by social/communal considerations which markedly restrict our ostensibly unfettered freedom of expression and opinion. Ultimately, Fish argues that in every situation some incontrovertible assumptions and principles are at work (including the assumption of an intention, which makes our utterances intelligible) even though in a different situation we may be capable of questioning and relativizing them. The point of the essay "From Conventionalism to Normativism" is thus to indicate the evolutionary emergence of normative categories in Fish's critical vocabulary, which has contained the seeds of his current position even in his most radical attacks on formalism and essentialism in the 1970s and 1980s.